Great sermons on the resurrection of Christ : by celebrated preachers : with biographical sketches and bibliographies (Natick, MA : W.A. Wilde, 1964)
Includes sermons from various preacers with biographical notes for each, and bibliographical references.
Keywords: McIlvaine, Charles Pettit, -- 1799-1873; Spurgeon, Charles Haddon, -- 1834-1892; Hayes, Doremus A. -- 1863-1936; Young, Dinsdale T. -- 1861-1937; Morgan, George Campbell, -- 1863-1945; Liddon, Henry Parr, -- 1829-1890; Gurney, Thomas Alfred, -- 1856-1927(?); Bruce, Alexander B. -- 1831-1899; Saphir, Adolph, -- 1831-1891; Findlay, George G. -- 1849-1919; Westcott, Brooke Foss, -- 1825-1901; Candlish, Robert S. -- 1806-1873; Meyer, Frederick Brotherton, -- 1847-1929; Broadhus, John R. -- 1827-1895; Jesus Christ -- resurrection